Scoping Review of Epidemiological Studies on Carcinogenic Metals in Soil and Cancer Burden in General Population - Joanna Julia Bartnicka; Felipe Yunta Mezquita; Francisco Rodriguez Rasero; Giorgia Randi; Tadeusz Dyba; Raquel Carvalho (Exposure and Health, 2026)

Influences of outliers on performance of geographically weighted random forest for modelling cadmium concentrations in topsoil of the northern part of Ireland - Yunfan Li; Yuqi Zhang; Haofan Xu; Felipe Yunta-Mezquita; Diana Vieira; Chaosheng Zhang (Journal of Hazardous Materials, 2026)

Warming could cause significant soil organic carbon loss around the southern Baltic Sea - Yunfan Li; Panos Panagos; Felipe Yunta Mezquita; Chaosheng Zhang (Journal of Environmental Management, 2025)

Opportunities for optimizing phosphorus inputs in EU agricultural soils - Elise Van Eynde; Gerard H. Ros; Felipe Yunta; Anna Muntwyler; Philippe Hinsinger; Arthur N. Fendrich; Panos Panagos (Environmental Science & Policy, 2025)

Microbial biomass carbon distribution under agroforestry practices and soil depth variations in Southern Ethiopia - Nebiyou Masebo; Emiru Birhane; Serekebirhan Takele; Juan J. Lucena; Pérez-Sanz Araceli; Felipe Yunta; Zerihun Belay; Agena Anjulo (Agroforestry Systems, 2025)

Management of excavated soil and dredging spoil waste from construction and demolition within the EU: Practices, impacts and perspectives - Jorge Cristóbal; Gillian Foster; Dario Caro; Felipe Yunta; Simone Manfredi; Davide Tonini (Science of The Total Environment, 2024)

A Systematic Review and Characterization of the Major and Most Studied Urban Soil Threats in the European Union - Hannah Binner; Piotr Wojda; Felipe Yunta; Timo Breure; Andrea Schievano; Emanuele Massaro; Arwyn Jones; Jennifer Newell; Remigio Paradelo; Iustina Popescu Boajă; Edita Baltrėnaitė-Gedienė; Teresa Tuttolomondo; et al. (Water, Air, & Soil Pollution, 2024)
There is an urgent need by the European Union to establish baseline levels for many widespread pollutants and to set out specific levels for these under the Zero pollution action plan. To date, few systematic reviews, superseded by bibliometric analyses, have explored this issue. Even less research has been carried out to compare the efficacy of these two data extraction approaches. This study aims to address these two issues by i) constructing an inventory of the available information on urban soils, highlighting evidence gaps and measuring compliance with the Zero pollution action plan, and by ii) comparing the methods and results of these two data extraction approaches. Through Scopus and Web of Science databases, peer-reviewed articles using the terms urban soil in combination with specific urban soil threats and/or challenges were included. Notably, both approaches retrieved a similar number of initial articles overall, while the bibliometric analysis removed fewer duplicates and excluded fewer articles overall, leaving the total number of articles included in each approach as: 603 articles in the systematic review and 2372 articles in the bibliometric analysis. Nevertheless, both approaches identified the two main urban soil threats and/or challenges to be linked to soil organic carbon and/or heavy metals. This study gives timely input into the Zero pollution action plan and makes recommendations to stakeholders within the urban context.

Quantitative analysis of the compliance of EU Sewage Sludge Directive by using the heavy metal concentrations from LUCAS topsoil database - Felipe Yunta; Calogero Schillaci; Panos Panagos; Elise Van Eynde; Piotr Wojda; Arwyn Jones (Environmental Science and Pollution Research, 2024)
In the European Union (EU), a common understanding of the potential harmful effect of sewage sludge (SS) on the environment is regulated by the Sewage Sludge Directive 86/278/EEC (SSD). Limit values (LVs) for concentrations of heavy metals in soil are listed in Impact Assessment of this directive, and they were transposed by EU member states using different criteria. Member states adopted either single limit values or based on soil factors such as pH and texture to define the maximum limit values for concentrations of heavy metals in soils. Our work presents the first quantitative analysis of the SSD at the European level by using the Land Use and Coverage Area Frame Survey (LUCAS) 2009 topsoil database. The reference values at the European level were arranged taking into account the upper value (EU_UL) and the lower value (EU_LL) for each heavy metal (arsenic, cadmium, copper, chromium, mercury, nickel, lead, and zinc) as well as taking into account the pH of the soil (cadmium, copper, mercury, nickel, lead, and zinc) as introduced in the SSD Annex IA. Single and integrated contamination rate indices were developed to identify those agricultural soils that exceeded the reference values for each heavy metal. In total, 10%, 36%, and 19% of the LUCAS 2009 topsoil samples exceeded the limit values. Additionally, 12% and 16% of agricultural soils exceeded the concentration of at least one single heavy metal when European LVs were fixed following the soil pH in Strategy II compared to those national ones in Strategy I. Generally, all member states apply similar or stricter limit values than those laid down in the SSD. Our work indicates that choosing LVs quantitatively affects further actions such as monitoring and remediation of contaminated soils. The actual soil parameters, such as heavy metal concentrations and soil pH values from the LUCAS 2009 topsoil database, could be used by SSD-involved policy stakeholders not only to lay down the LVs for concentrations of heavy metal in soils but also for monitoring the SSD compliance grade by using the LUCAS surveys over time (past and upcoming LUCAS datasets).

Effectiveness of Ethylenediamine-N(o-hydroxyphenylacetic)-N′(p-hydroxyphenylacetic) acid (o,p-EDDHA) to Supply Iron to Plants - Sonia García-Marco; Noelia Martínez; Felipe Yunta; Lourdes Hernández-Apaolaza; Juan J. Lucena (Plant and Soil, 2006)